The increase in bone mineral density by bisphosphonate with active vitamin D analog is associated with the serum calcium level within the reference interval in postmenopausal osteoporosis. Issue 1 (2nd January 2019) - Kinoshita, Mayuko; Ishijima, Muneaki; Kaneko, Haruka; Liu, Lizu; Nagao, Masashi; Sadatsuki, Ryo; Hada, Shinnosuke; Arita, Hitoshi; Aoki, Takako; Yamanaka, Makoto; Nojiri, Hidetoshi; Sakamoto, Yuko; et al.
Abstract: Objectives: To examine the factors associated with increase in lumbar spine bone mineral density (LS-BMD) by bisphosphonates (BPs) with active vitamin D analog (aVD). Methods: Two independent postmenopausal osteoporotic patients treated by BPs with aVD for 24 months (Study 1: n = 93, Study 2: n = 99) were retrospectively analyzed. Results: In Study 1, LS-BMD of the patients significantly increased for 24 m (5.4%, p < .001). A multiple regression analysis among baseline characteristics revealed that serum calcium (sCa: 8.5–10.5 mg/dL) was associated with an increased LS-BMD by treatment ( r 2 : 0.088, p = .02). While average sCa of the patients was 9.2 mg/dL before treatment, it increased time-dependently to 9.6 mg/dL for 24 m by treatment. As each patient had their LS-BMD five times during the study, there were four instances of %LS-BMD in each patient, resulting in 372 instances of %LS-BMD in Study 1. The smallest Akaike's information criterion value for the most appropriate cut-off levels of sCa for %LS-BMD by treatment every 6 m was 9.3 mg/dL. The %LS-BMD by treatment for 6 m during 24 m period in patients with sCa ≥9.3 mg/dL (1.5%) was significantly higher than that in patients with sCa <9.3 mg/dL (0.8%, p = .038). The results of Study 2 were similar to those of Study 1, confirming the phenomena observed. Conclusion: sCa was associated with an increased LS-BMD by BPs with aVD.